2019
DOI: 10.3892/ijmm.2019.4400
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic mast cells accelerate the proliferation, collagen accumulation and phenotypic alteration of human lung fibroblasts

Abstract: Pulmonary vascular remodeling and fibrosis are the critical pathological characteristics of hypoxic pulmonary hypertension. Our previous study demonstrated that hypoxia is involved in the functional alteration of lung fibroblasts, but the underlying mechanism has yet to be fully elucidated. The aim of the present study was to investigate the effect of mast cells on the proliferation, function and phenotype of fibroblasts under hypoxic conditions. Hypoxia facilitated proliferation and the secretion of proinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…We have characterized the signaling pathway mediating dormancy and ECM remodeling through COLIII/DDR1/STAT1 and identify DDR1 as the receptor for Collagen Type III that drive activation of dormancy. While the mechanisms that regulate COL3A1 and DDR1 expression are not well understood, recent reports identified hypoxia as a regulator of collagen type III expression 52,53 . Also analysis of the hypoxic transcriptome of head and neck cancer cells showed that DDR1 expression increased upon hypoxia (GSE87456 from Brady et al, 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have characterized the signaling pathway mediating dormancy and ECM remodeling through COLIII/DDR1/STAT1 and identify DDR1 as the receptor for Collagen Type III that drive activation of dormancy. While the mechanisms that regulate COL3A1 and DDR1 expression are not well understood, recent reports identified hypoxia as a regulator of collagen type III expression 52,53 . Also analysis of the hypoxic transcriptome of head and neck cancer cells showed that DDR1 expression increased upon hypoxia (GSE87456 from Brady et al, 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, HIF-1 α was found to be active in fibroblasts from IPF patients and induced myofibroblast differentiation with the existence of TGF- β ( 24 , 26 , 29 , 30 ). It is worth mentioning that hypoxia facilitated proliferation and the secretion of proinflammatory cytokines in mast cells, and thus influenced fibrogenesis ( 31 ). In IPF, alveolar macrophages showed a perturbation of mitochondria homeostasis, including increased mitochondria reactive oxygen species (mtROS), in which HIF-1 α may have participated ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory mechanisms concerning airway remodeling during asthmatic conditions can involve dysregulated processes in all 3 layers of the airway wall. 6 In particular, numerous studies have identified a major effector role for the smooth muscle cells (SMCs) during asthma exacerbations with excessive airway narrowing. However, asthmatic responses can also be related to events occurring in the airway submucosa.…”
mentioning
confidence: 99%